An Update of Palmitoylethanolamide and Luteolin Effects in Preclinical and Clinical Studies of Neuroinflammatory Events - Marika Cordaro; Salvatore Cuzzocrea; Rosalia Crupi (Antioxidants, 2020)
The inflammation process represents of a dynamic series of phenomena that manifest themselves with an intense vascular reaction. Neuroinflammation is a reply from the central nervous system (CNS) and the peripheral nervous system (PNS) to a changed homeostasis. There are two cell systems that mediate this process: the glia of the CNS and the lymphocites, monocytes, and macrophages of the hematopoietic system. In both the peripheral and central nervous systems, neuroinflammation plays an important role in the pathogenesis of neurodegenerative diseases, such as Parkinson’s and Alzheimer’s diseases, and in neuropsychiatric illnesses, such as depression and autism spectrum disorders. The resolution of neuroinflammation is a process that allows for inflamed tissues to return to homeostasis. In this process the important players are represented by lipid mediators. Among the naturally occurring lipid signaling molecules, a prominent role is played by the N-acylethanolamines, namely N-arachidonoylethanolamine and its congener N-palmitoylethanolamine, which is also named palmitoylethanolamide or PEA. PEA possesses a powerful neuroprotective and anti-inflammatory power but has no antioxidant effects per se. For this reason, its co-ultramicronization with the flavonoid luteolin is more efficacious than either molecule alone. Inhibiting or modulating the enzymatic breakdown of PEA represents a complementary therapeutic approach to treating neuroinflammation. The aim of this review is to discuss the role of ultramicronized PEA and co-ultramicronized PEA with luteolin in several neurological diseases using preclinical and clinical approaches.